Faktor-Faktor Yang Mempengaruhi Cadangan Devisa Indonesia - Stella Yulia Cancer; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
This study aims to analyze in the short and long term the effect of exports,exchange rate and froreign direct investment (FDI) on foreign exchangereserves in Indonesia. This type of research is quantitative research usingsecondary data. The data analysis method used is the Auto RegressiveDistributed Lag (ARDL). The variables used are Foreign Reserves (Y), Exports(X1), Exchange Rate (X2) and Foreign Direct Investment (X3). The data used isthe time series period 1989-2020 obtained from relevant institutions andagencie. The results of this study indicate that all independent variablestogether have a significant effect on foreign exchange reserves as the dependentvariable. In the short-term test, the export variable has a positive andsignificant effect on foreign exchange reserves. Exchange rate has a negativeand insignificant effect on foreign exchange reserves, while FDI has a negativeand significant effect on foreign exchange reserves. In the long term, the exportvariable has a negative and significant effect on foreign exchange reserves. Theexchange rate has a positive and significant effect on foreign exchange reserves,while FDI has a positive and significant effect on foreign exchange reserves.